Case reportUnusual skin manifestation of Sweet syndrome - Obtułowicz, Aleksander; Sułowicz, Joanna; Jaworek, Andrzej; Wojas-Pelc, Anna; Stompór, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
In 1986 two major and two minor diagnostic criteria of Sweet syndrome were proposed by Su and Liu. In this paper we report a case of Sweet syndrome manifested as erythema nodosum-like lesions without a tendency for disintegration, but with pustules predominantly on the surface of the face. The mentioned lesions occurred after a few days of treatment with azathioprine. This drug was introduced by the nephrologist due to symptoms of nephrotic syndrome of unknown background, lasting for more than one year. For more than thirty years the patient has been treated (mostly surgically) for recurrent perirectal fistula. Because of the long-lasting inflammation in this area secondary (AA-type) amyloidosis was considered as the most likely reason for the kidney damage (although the histological assessment of the gingival biopsy sample did not confirm such a diagnosis and a kidney biopsy was not considered due to the poor general status of the patient and advanced kidney failure). On admission to the dermatology department the patient suffered from pronounced generalized weakness, but without fever or arthralgia. Moderately enlarged cervical lymph nodes were found in the physical exam. Additional lab tests revealed decreased creatinine clearance, thus confirming the diagnosis of advanced kidney failure. In the histological assessment of the skin abundant neutrophilic infiltrates were found with no evidence of vasculitis. Gradual resorption of skin lesions was obtained after treatment with prednisone in the initial dose of 50 mg/day. We suggest that the described case of Sweet syndrome with an unusual clinical course represents a skin manifestation of the chronic inflammatory process secondary to long-lasting recurrent perianal fistulas in a patient with concomitant advanced chronic kidney disease.